Thermoregulation in wheelchair tennis - How to manage heat stress? - Girard, O. (Frontiers in Physiology, 2016)
Founded in 1976 and having become a full medal sport at the 1992 Barcelona Paralympics, the popularity of wheelchair tennis continues to grow. With the exception of the "double-bounce rule," wheelchair and able-bodied tennis follow the same rules. Most of tennis matches are played in cool outdoor conditions or climate-controlled indoor venues. Nonetheless, it is common for top-level players to be exposed to hot (>30°C) and/or humid (>70% rH) conditions during competition or training [Wet Bulb Globe Temperature (WBGT) of 28°C or greater]. At the 2009 Australian Open championship, Australia's former world No 1 Daniela Di Toro, spoke about the high court temperatures (often above 40°C)—"You've got the direct heat overhead as well as radiant heat all around you that has been absorbed by the court and your chair, and it really is extremely full-on." Heat stress may not only threaten the quality of play, but could potentially pose a risk to the players' health. Detailed description of thermal, physiological and perceptual responses of able-bodied players to simulated competitions can be found in the literature (Fernandez Fernandez et al., 2006), while the investigations that have involved Paralympic tennis players are rare. Evaluating the specific game requirements is a prerequisite of more thoroughly understanding the physiology of wheelchair tennis. This task is, however, not easy due to numerous modulating internal (i.e., variety of physiological impairment, competitive standard, playing style, gender and body composition) and external (i.e., environmental conditions, ball type and court surface) factors of tennis match intensity, in addition to high individual variability in physiological responses to match play. Moreover, it is difficult to develop and implement universal safety standards and guidelines to account for all of the environmental scenarios. Well aware of potential health risks, the International Tennis Federation (ITF) medical commission has implemented policies for effectively reducing heat illness risk to safeguard wheelchair tennis players' health when competing in environmentally challenging conditions (http://www.itftennis.com/media/166656/166656.pdf). In addition to these existing procedures in wheelchair tennis the question still exist as to what preventive countermeasures can be implemented when it gets hot.